Online Impulse Buying: The Application of Srimulus-Organism-Response Model - Azzahra Anandita Prasetya; Rini Kuswati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the application of the Stimulus-Organism-Response (S-O-R) model to understand how social media marketing influences online impulse buying among Generation Z fashion consumers. Social media marketing activities, including interaction, entertainment, trendiness, word-of-mouth, and personalization, are considered as the stimulus, while impulse buying intention is the dependent variable. Brand resonance and emotional response serve as mediators and social network proneness acts as a moderator. Data was collected through online questionnaires to ensure reliability and consistency. The analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS, which validated the measurement and structural relationships. The results reveal that while social media marketing activities influence emotional responses and brand resonance, these factors alone do not directly drive impulse buying. Instead, emotional responses, particularly positive emotions, have a stronger impact on impulse buying intentions. Social network proneness also plays a role in making consumers more responsive to recommendations, though it does not mediate the relationship between marketing activities and purchase intentions. The study highlights the complexity of online impulse buying behavior, with emotional and situational factors being crucial drivers. Limitations include a sample focused on a specific demographic in the fashion industry, which may affect generalizability. Future research should explore generational differences, psychological motivations, and the impact of technology and visual content, as well as investigate other moderators influencing impulse buying behavior.